Harnessing visible-light and limited near-IR photons through plasmon effect of gold nanorod with AgTiO2 - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
The utilization of the red-green-blue (RGB) and limited near-IR photons for solar hydrogen evolution (SHE) has been reported in a single plasmonic nanocomposite. Present study describes the use of AgTiO2 (AgT) decorated with Au nanorods (AgT-AuNR) to enhance the absorption of entire visible-light and limited near-IR wavelength range in the sunlight for SHE from photocatalytic water splitting reaction. It is demonstrated that the longitudinal plasmon resonance of AuNR in AgT-AuNR induces SHE between 550 and 800 nm, whereas TiO2-AuNR or AgT shows no activity in this wavelength range. The key aspect of achieving the high photocatalytic activity of AgT-AuNR in the solar spectrum is the electronic integration among metal NPs as well as with TiO2, and the heterojunctions among them. Presence of such heterojunctions has been supported by different characterization studies. However, gold nanorod exhibits field effect and further enhances light harvesting. Although the absolute amount of energy harvested only from near-IR photons is low, when combined with high-energy visible-light photons within one sun conditions, it shows a multiplier effect rather than a simple additive effect. Likely, this is the first report, where SHE has been achieved with significant amount of light absorption at lambda >= 550 nm with a plasmonic nanocomposite.